2015
DOI: 10.1371/journal.pone.0141786
|View full text |Cite
|
Sign up to set email alerts
|

Client Proteins and Small Molecule Inhibitors Display Distinct Binding Preferences for Constitutive and Stress-Induced HSP90 Isoforms and Their Conformationally Restricted Mutants

Abstract: The two cytosolic/nuclear isoforms of the molecular chaperone HSP90, stress-inducible HSP90α and constitutively expressed HSP90β, fold, assemble and maintain the three-dimensional structure of numerous client proteins. Because many HSP90 clients are important in cancer, several HSP90 inhibitors have been evaluated in the clinic. However, little is known concerning possible unique isoform or conformational preferences of either individual HSP90 clients or inhibitors. In this report, we compare the relative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 54 publications
4
46
0
1
Order By: Relevance
“…To determine the relative binding strength of Bio-GBA to Hsp90 isoforms and their mutants, we followed a modified version of the LUMIER method, as previously described (8). Briefly, HEK293 cells were transfected with each 3×F-Hsp90 expression plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the relative binding strength of Bio-GBA to Hsp90 isoforms and their mutants, we followed a modified version of the LUMIER method, as previously described (8). Briefly, HEK293 cells were transfected with each 3×F-Hsp90 expression plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…There are two major cytoplasmic isoforms of Hsp90: the stress-inducible Hsp90α and the constitutively expressed Hsp90β. These isoforms share 85% sequence identity and display significant functional redundancy, although each paralog has also developed distinct cellular functions during evolution (7,8). Unfortunately, current pharmacologic approaches do not allow interrogation of isoformspecific function, because currently available agents are not able to clearly distinguish between Hsp90α and Hsp90β (9).…”
mentioning
confidence: 99%
“…For example, we know that solid support immobilized versions of several such inhibitors precipitate distinct HSP90 pools (Moulick et al, 2011, Prince et al, 2015). 17-AAG and NVP-AUY-922 but not PU-H71 (Figure 1A) augment the phenotype observed when cancer cells are treated with a compound that disrupts the HSP90-HOP interaction (Pimienta et al, 2011).…”
Section: Hsp90 Probesmentioning
confidence: 99%
“…Lastly, using a defined set of HSP90 conformational mutants, the authors found that some clients interact strongly with a single, ATP-stabilized HSP90 conformation, only transiently populated during the dynamic HSP90 chaperone cycle, while other clients interact equally with multiple HSP90 conformations. GM and STA9090 (ganetespib) were differentially able to access these HSP90 conformational states (Prince et al, 2015). Taldone et al used an FITC-labeled HSP90 probe coupled with fluorescence polarization and combined it with computational analyses to rationalize such differences at the structural level (Taldone et al, 2013a).…”
Section: Hsp90 Probesmentioning
confidence: 99%
“…N-terminal Hsp90 inhibitors can also show a preferential interaction with SUMOylated versus non-SUMOylated Hsp90, resulting in greater activation of a HSR [42•]. Lastly, drug efficacy may also be influenced by the isoform ratio of chaperone complexes since N-terminal inhibitors can bind Hsp90β with greater affinity than Hsp90α [43]. Collectively, these data raise the possibility that the onset of disease may increase or possibly negate the therapeutic potential of various inhibitors by altering their recognition or interaction with Hsp90 isoforms and their heteroprotein complexes.…”
Section: Pharmacologic Targeting Of Hsp90—the Fit and The Form Begetsmentioning
confidence: 99%